2008
DOI: 10.2136/sssaj2007.0248
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Harvesting Maize Stover and Tillage on Soil Quality

Abstract: Rising concerns about greenhouse gases, increased fuel prices, and the potential for new high value agricultural products have raised interest in the use of maize stover for bioenergy production. However, residue harvest must be weighed against potential negative impacts on soil quality. This study, conducted in Chazy, NY, evaluated the long‐term effects of 32 yr of maize (Zea mays L.) stover harvest vs. stover return on soil quality in the surface layer (5–66 mm) under plow till (PT) and no‐till (NT) systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 53 publications
10
185
2
1
Order By: Relevance
“…As the amount of stover harvest increased, SRP values increased steadily from 1.55 to 2.16 MPa, but due to variability in the data, only the noand high-harvest treatments were statistically different at p < 0.05 (Table 2). These results are not consistent with those of Karlen et al (1994) or Moebius-Clune et al (2008) who did not find any detectable, adverse effects of stover harvest on SRP. However, reported that SRP increased as stover harvest rates increased.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…As the amount of stover harvest increased, SRP values increased steadily from 1.55 to 2.16 MPa, but due to variability in the data, only the noand high-harvest treatments were statistically different at p < 0.05 (Table 2). These results are not consistent with those of Karlen et al (1994) or Moebius-Clune et al (2008) who did not find any detectable, adverse effects of stover harvest on SRP. However, reported that SRP increased as stover harvest rates increased.…”
Section: Resultscontrasting
confidence: 97%
“…Our results indicate that regardless of corn stover harvest, no-tillage had higher Bd than chisel plow (Table 1). Soil bulk density was impacted more by tillage practice than stover harvest as previously reported by Moebius-Clune et al (2008). Lower Bd with chisel plowing is attributed to annual loosening of the soil surface, whereas higher Bd with no-tillage reflects the absence of soil mechanical fracturing as suggested by Malhi (2006), Guedes Filho et al (2013) and Villamil et al (2015).…”
Section: Resultssupporting
confidence: 58%
“…Second, univariate statistics of biological indicators may be of limited use in the context of evaluating soil quality, because they only characterize a system at the overall scale and do not account for spatial patterns [23]. Finally, even if we account for the spatial and temporal variability of biological indicators, the precise relationship between the amount of a particular biological indicator and it's functional characteristics has yet to be determined [31]. These problems can become critical when using the MVIK procedure to evaluate specific criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Tree roots at the seaward edge may be oxygen-limited due to the mangrove mud being anoxic, where the presence of taller and more abundant pneumatophores rising above the mud will help transport oxygen to the submerged roots and by the development of internal gas transport pathways extending throughout the entire root system and communicating with the air by means of lenticels or other specialized water exuding structures [11] . Soil quality is one of the most important factors in sustaining the global biosphere and developing sustainable agricultural practices [7] . It has been defined in several different ways in recent years from view points of bioproductivity, sustainability, environmental protection, and human and animal health.…”
Section: Soluble Cations (%) Soluble Anions (%) ---------------------mentioning
confidence: 99%
“…Many practices greatly impact the direction and degree of soil quality changes in time and space. Understanding the effects of these practices on soil quality and its indicators has been identified as one of the most important goals for modern soil science and plant growth [7] . Soils at Al-Jubail Area are subjected to long-term damage and might gradually decrease its soil quality over the years.…”
Section: Soluble Cations (%) Soluble Anions (%) ---------------------mentioning
confidence: 99%